Presence and Profiles of Women on Corporate Boards in Philippine Publicly Listed Corporations: A Resource Dependence Theory Perspective - Lizares, Regina M. (Philippine Management Review; Vol 30 (2023), 2023)
Using a resource dependence perspective, this study investigates meso-level factors influencing the likelihood of a woman director (WOCBs) in Philippine publicly listed corporations (PLCs) and identifies profiles of WOCB based on the resources they provide a firm. Employing a sample of 252 PLCs and logistic analysis, this study determines that board size is significant and positively associated with the likelihood of a WOCB. Furthermore, utilizing the biographical data of 456 WOCB and cluster analysis, this study identifies five profiles of WOCB and determines the dominance of WOCBs who have a profile of a business expert.